Comparison of Functional Status and Depression in Younger and Older Patients with Chronic Low Back Pain: A Multi-center Crosssectional Survey - Yasemin Yumuşakhuylu; Afitap İçağasıoğlu; Naciye Füsun Toraman; Gülçin Kaymak Karataş; Ömer Kuru; Yeşim Kirazlı; Kazım Çapacı; Esma Eriman; Sema Haliloğlu; Ayşegül Ketenci (Galenos Yayinevi, 2024)
Objective: This study compared the differences in functionality and depression between younger and older patients with chronic low back pain (CLBP). Materials and Methods: This multi-center cross-sectional survey enrolled subjects with CLBP who visited physical medicine and rehabilitation clinics in seven different regions of Turkey. Sociodemographic data were collected via questionnaires. Functional status was evaluated with Roland-Morris Disability index (RMDI), and psychological health was evaluated with Beck Depression inventory (BDI). Results: The sample included 106 younger [mean age: 24.3 (range: 18-30) years] and 104 older [mean age: 70.5 (range: 65-108) years] subjects. No significant difference was found in the gender distribution between the younger (38 males, 68 females) and older (38 males, 66 females) groups (p=0.917). The BDI was 11.90±10.6 in the younger subjects and 16.17±10.72 in the older subjects (p=0.002), whereas the mean RMDIs were 10.31±6.36 and 16.04±5.36, respectively (p=0.001). Conclusion: The loss of functional capacity and depression resulting from CLBP are serious threats to public health and are predictive of chronic disability. The development of social programs that address risk factors will reduce the risk of CLBP, improve quality of life, reduce workforce losses and contribute significantly to public health.